Faktor-Faktor Yang Mempengaruhi Peningkatan Kualitas Pelayanan Kesehatan Di Instalasi Gawat Darurat: Studi Teoritis - Intan Permatasari Situmorang; Dety Mulyanti (Journal of Management and Social Sciences, 2023)
The emergency department is the front door in providing patient safety and health services. An emergency department certainly requires a fast and precise approach to patient safety. Fast and precise handling will increase patient satisfaction, patient satisfaction is a condition where the patient's needs, desires and expectations can be met through the products and services consumed. Therefore patient satisfaction is a measure of the quality of service felt by patients divided by the patient's needs, patient desires, and expectations of the patient himself. The purpose of writing this scientific article is to find out and review from a theoretical point of view various literatures. The method used is a theoretical study by analyzing and comparing existing theories. The result of this theoretical study is its function to review the factors that become patient satisfaction, so that it can assist the Hospital in making a better plan with a more logical, rational and systematic approach for each option that will be found by forming a plan. So that it can improve the image and trust of patients in choosing health care facilities. For the hospital it is very important and needs to be done optimally with these patient satisfaction factors to support the improvement of the hospital's status. So the agency in terms of tangible, reliable, assurance, and empathy to improve patient quality.